2024
DOI: 10.1021/jacs.3c13602
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Induced Interfacial Hydrophobic Microenvironment Promotes the C–C Coupling in Electrochemical CO2 Reduction

Xinzhe Yang,
Haowen Ding,
Shunning Li
et al.

Abstract: The electrochemical carbon dioxide reduction reaction (CO 2 RR) toward C 2 products is a promising way for the clean energy economy. Modulating the structure of the electric double layer (EDL), especially the interfacial water and cation type, is a useful strategy to promote C−C coupling, but atomic understanding lags far behind the experimental observations. Herein, we investigate the combined effect of interfacial water and alkali metal cations on the C−C coupling at the Cu(100) electrode/electrolyte interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…As shown in Table S2, the present Cu-F-M electrocatalyst exhibits better or comparable catalytic performance for the eCO 2 RR in terms of ethanol selectivity and current density in comparison to previously reported Cu-based electrocatalysts. In addition, as demonstrated in Figure S7b, after surface hydrophobic modification by sodium laurate, the hydrogen Faraday efficiency on Cu-F-M is reduced by more than 30% when compared to the Cu-F catalyst, attributable to the effective inhibition of the hydrogen evolution competition reaction by the hydrophobic surface, weakening the adsorption of *H, thereby enhancing the proportions of carbonic products (including ethanol) in the products of the eCO 2 RR. Intriguingly, a small amount of n -propanol can be produced in the eCO 2 RR across all Cu-based electrocatalysts examined (Figure S7b,c), demonstrating the potential of present oxide-derived Cu-based electrocatalysts in transforming CO 2 into three-carbon products in the eCO 2 RR. , In addition, the Nyquist plots of Cu-based electrocatalysts (Figure S7d) reveal that the Cu-F-M catalyst has a medium charge transfer resistance among them. Furthermore, to eliminate the potential interference of surface-decorated sodium laurate on modified Cu-based electrocatalysts in the eCO 2 RR, a Cu-F-M catalyst was placed in an electrolyte containing 0.02 M sodium laurate.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Table S2, the present Cu-F-M electrocatalyst exhibits better or comparable catalytic performance for the eCO 2 RR in terms of ethanol selectivity and current density in comparison to previously reported Cu-based electrocatalysts. In addition, as demonstrated in Figure S7b, after surface hydrophobic modification by sodium laurate, the hydrogen Faraday efficiency on Cu-F-M is reduced by more than 30% when compared to the Cu-F catalyst, attributable to the effective inhibition of the hydrogen evolution competition reaction by the hydrophobic surface, weakening the adsorption of *H, thereby enhancing the proportions of carbonic products (including ethanol) in the products of the eCO 2 RR. Intriguingly, a small amount of n -propanol can be produced in the eCO 2 RR across all Cu-based electrocatalysts examined (Figure S7b,c), demonstrating the potential of present oxide-derived Cu-based electrocatalysts in transforming CO 2 into three-carbon products in the eCO 2 RR. , In addition, the Nyquist plots of Cu-based electrocatalysts (Figure S7d) reveal that the Cu-F-M catalyst has a medium charge transfer resistance among them. Furthermore, to eliminate the potential interference of surface-decorated sodium laurate on modified Cu-based electrocatalysts in the eCO 2 RR, a Cu-F-M catalyst was placed in an electrolyte containing 0.02 M sodium laurate.…”
Section: Resultsmentioning
confidence: 98%
“…This scenario is analogous to the formation of hydrophobic layers and the suppression of water reduction caused by organic coating or ion assembly on electrode surfaces in aqueous systems. 25,61,62…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there has been a resurgence in interest in studying how electrolyte properties also influence electrocatalytic reactions, 17–19 and many recent studies have shown that the properties of electrolytes can play at least an equally important role as electrodes in controlling reaction activity and selectivity. For instance, strategies such as increasing electrolyte pH, 20–23 changing the identity of supporting cations, 24–26 and decreasing water activity by increasing electrolyte concentration have been employed to enhance both the overall CO 2 conversion selectivity versus water reduction and the selective generation of multi-carbon products. 27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the confirmation of the local coordination environment of Cu 1 , we then investigated its reaction process by focusing on two key steps, i.e., *CO → *CHO and CO–CO coupling. *CHO formation on Cu 1 @C 3 N 4 through the Eley–Rideal (ER) mechanism is endothermic with an insurmountable E a of 1.81 eV. The adsorption of the second CO molecule on Cu 1 @C 3 N 4 is slightly endothermic (Figure c), and *CO coupling is unfavorable, given that its E a is 1.29 eV.…”
mentioning
confidence: 99%